Management of Immunization in Public Health Center Related to The Universal Child Immunization (UCI) in Arjowinangun Health Center, Malang - Ummah, Wiqodatul; Munawir, Al; Ningtyias, Farida Wahyu (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
a